Spark : how genius ignites, from child prodigies to late bloomers - Kalb, Claudia (National Geographic Partners, LLC, 2021)
Offers thirteen linked biographies of individuals from history and the present who are considered to be geniuses and tracking when and why at certain points in their lives they seem to have developed their spark of talent--from child acting star Shirley Temple to Peter Mark Roget, the famous thesaurus compiler who got his start in his seventies. Explores the relationships of willpower, brains, talent, and circumstance in these thirteen genius individuals.